Sintering Behavior of CNT Reinforced Al6061 and Al2124 Nanocomposites - Nouari Saheb (Advances in Materials Science and Engineering)
Ball milling and spark plasma sintering were successfully used to produce carbon nanotube reinforced Al6061 and Al2124 nanocomposites which have potential applications in the fields of aerospace, automotive, electronics, and high precision instrumentation. Al2124 and Al6061 nanocomposite powders containing 0.5 to 2 wt.% CNTs prepared through sonication and wet ball milling were spark plasma sintered at 400, 450, and 500°C for 20 minutes under a pressure of 35 MPa. CNTs were better dispersed, and less agglomerated and had good adhesion to the matrix in composites containing 1 wt.% CNTs. The increase of CNT content to 2 wt.% led to the formation of CNT clusters which resulted in less uniform and homogenous composite powders. Almost full densification of Al6061 reinforced with CNTs was achieved at 500°C. Also, CNTs reinforced Al2124 nanocomposites reached very high densities at 500°C. Composites reinforced with 1 wt.% CNTs displayed better densification compared to composites containing 2 wt.% CNTs. The increase of CNTs content from 0.5 to 1 wt.% increased the hardness of the Al6061 and Al2124 alloys to maximum values. Further increase of CNTs content to 2 wt.% decreased the hardness to values lower than that of the monolithic alloys.